Tumor immune microenvironment and genomic evolution in a patient with metastatic triple negative breast cancer and a complete response to atezolizumab - Luciana Molinero; Yijin Li; Ching-Wei Chang; Sophia Maund; Maureen Berg; Jeanne Harrison; Marcella Fassò; Carol O’Hear; Priti Hegde; Leisha A. Emens (Journal for ImmunoTherapy of Cancer, 2019)
Abstract Background Metastatic TNBC (mTNBC) has a poor prognosis and few treatment options. The anti-PD-L1 antibody atezolizumab demonstrated clinical activity in mTNBC patients with PD-L1-positive tumor-infiltrating immune cells. The current study describes the tumor immune microenvironment (TiME) and genomic evolution across sequential therapies in a patient with a 31-year history of TNBC and a complete response (CR) to atezolizumab monotherapy. Materials and methods In 1986, the patient had surgery and radiotherapy (XRT) for newly diagnosed TNBC, followed by surgery and adjuvant chemotherapy for two locoregional recurrences. She developed mTNBC in 2009 and was sequentially treated with capecitabine, gemcitabine-carboplatin-iniparib (GCI), XRT and an experimental vaccine. She experienced disease progression (PD) to all these therapies. In 2013, she had a PD-L1 positive tumor and enrolled in a phase 1 atezolizumab monotherapy study (PCD4989g; NCT01375842). She received atezolizumab for 1 year with initial pseudo-progression followed by a partial response. After 1 year without treatment she experienced PD, reinitiated atezolizumab and subsequently achieved CR. Tumor specimens were collected at numerous times between 2008 and 2015 and assessed by immunohistochemistry, RNA-seq and DNA-seq. Results TiME biomarkers, including CD8, ICs and PD-L1 on IC, increased after capecitabine and remained high after GCI, XRT and through pseudo-progression on atezolizumab. At PD post-atezolizumab exposure, TiME biomarkers decreased but PD-L1 status remained positive. Immune-related RNA signatures confirmed these findings. TNBC subtyping revealed evolution from luminal androgen receptor (LAR) to basal-like immune activated (BLIA). Genomic profiling showed truncal alterations in RB1 and TP53, while the presence of other genomic alterations varied over time. Tumor mutational burden peaked after XRT and declined after atezolizumab exposure. Conclusions This case report describes the evolution of TiME and TNBC molecular subtypes/genomics over time with sequential therapies in a TNBC patient with a CR to atezolizumab monotherapy. These data suggest the TiME is pliable and may be manipulated to maximize response to immunotherapy (NCT01375842, https://clinicaltrials.gov/ct2/show/NCT01375842?term=NCT01375842&rank=1).